2008
DOI: 10.1038/ismej.2008.3
|View full text |Cite
|
Sign up to set email alerts
|

3D FISH for the quantification of methane- and sulphur-oxidizing endosymbionts in bacteriocytes of the hydrothermal vent mussel Bathymodiolus azoricus

Abstract: Dual endosymbioses involving methane- and sulphur-oxidizing bacteria occur in the gills of several species of mussels from deep-sea hydrothermal vents and cold seeps. Variations of total and relative abundances of symbionts depending on local environmental parameters are not yet understood, due to a lack of reliable quantification of bacteria in the host tissue. Here, we report the first attempt to quantify volumes occupied by each type of symbiont in bacteriocyte sections from a vent mussel, Bathymodiolus azo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 32 publications
7
83
1
Order By: Relevance
“…Although our data must be interpreted with caution as only one individual per experimental condition was analyzed, the fact that observations qualitatively agree with expected results is a strong indication that our set-up is appropriate for the enrichment of each endosymbiont. Recently, a 3D-FISH technique was employed to quantify the effect of a sulphide pulse in a similar experimental set-up, on the volume and relative abundance of symbionts in mussel gills (Halary et al, 2008). We herein provide a first indication that MOB also respond to a methane pulse.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Although our data must be interpreted with caution as only one individual per experimental condition was analyzed, the fact that observations qualitatively agree with expected results is a strong indication that our set-up is appropriate for the enrichment of each endosymbiont. Recently, a 3D-FISH technique was employed to quantify the effect of a sulphide pulse in a similar experimental set-up, on the volume and relative abundance of symbionts in mussel gills (Halary et al, 2008). We herein provide a first indication that MOB also respond to a methane pulse.…”
Section: Discussionmentioning
confidence: 78%
“…Duperron et al (2006) found that the MOB 16S rRNA phylotype was also shared between the two mussel species, and that vent chemistry could affect the relative abundance of SOB and MOB. The volume occupied by each type of symbiont present within V. Riou et al: Bathymodiolus azoricus' carbon fixation by chemosynthesis a bacteriocyte, quantified using 3D fluorescence in situ hybridization (FISH) technique, varies from vent site to vent site between B. azoricus specimens (Halary et al, 2008). However, although physiological activity of the symbionts was observed in gills of a hydrothermal vent Bathymodiolid from the Pacific (Fiala-Médioni et al, 1986;Nelson et al 1995), in the Southern MAR B. puteoserpentis (Robinson et al, 1998) and in live specimens of the seep Bathymodiolid from the Gulf of Mexico (Childress et al, 1986;Fisher and Childress, 1992;Kochevar et al, 1992 andLee andChildress, 1995), it has to date not been demonstrated in live specimens of B. azoricus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the specimens of cluster D investigated by Duperron et al (2008), this phylotype 1 was identical to one of the two 16S rRNA partial sequences of one specimen and displayed six differences to that of another. The phylogenetic relationships between symbiont sequences obtained from cluster D and phylotype 1 obtained herein from cluster C were well supported.…”
Section: Methodsmentioning
confidence: 97%